Does digital transformation improve firm performance? Evidence from Vietnamese VN30 firms during the COVID-19 pandemic - Dao, Thi Ho Huong (Edelweiss Applied Science and Technology, 2026)
Digital transformation is widely promoted as a strategy for enhancing firm resilience during crises, yet rigorous evidence from emerging markets remains limited. This study examines whether digital transformation is associated with improved operational performance among Vietnam’s leading listed corporations during the COVID-19 pandemic. We employ a Difference-in-Differences (DiD) framework using panel data for 30 VN30 firms over 2010–2024 (N = 429). Firms are classified into high and low digital transformation intensity groups based on a composite index of credit, operational, and liquidity risk indicators for 2020–2024. Return on assets (ROA) is the primary outcome, with macroeconomic and firm-level risk controls. The DiD estimator for the interaction between the post-COVID period and high digital transformation intensity is positive but not statistically significant (coefficient = 0.0121, p = 0.356), indicating no detectable short-term ROA gains. Formal pre-trend tests show that the parallel trends assumption does not fully hold in this sample (p = 0.008), which limits strict causal interpretation and suggests that estimates should be viewed as descriptive associations. The findings suggest that digital transformation may not translate into immediate profitability improvements for large Vietnamese firms, consistent with the “productivity paradox” and the need for longer adjustment horizons. Credit risk and liquidity management emerge as more important short-run performance drivers than digital investment. The study underscores the importance of explicit assumption testing in DiD applications and highlights that digital transformation benefits in emerging markets may require patient capital and extended implementation periods.